EARLY WARNING SYSTEM OF EXTERNAL SUSTAINABILITY OF AN ECONOMY: CASE OF UKRAINE - О. Bazhenova; І. Chornodid; Yu. Yarmolenko; О. Golubev (Фінансово-кредитна діяльність: проблеми теорії та практики)
Abstract. The paper deals with the early warning system that allows monitoring the external sustainability of an economy due to external economic shocks. For this purpose, the analysis of the external sustainability indicators system of an economy (example of Ukraine) was implemented. It consisted of statistical analysis of the system of indicators of external sustainability of an economy, probabilistic assessment of their dynamics due to external economic shocks. The analysis of external sustainability indicators includes verifying their volatility, stability and variability relative to GDP. It means calculation of standard deviation for testing the volatility, autocorrelation to check the stability of the indicator and correlation between its value and GDP growth rate to measure the variability relative to the economy’s performance. The calculations of threshold percentiles for indicators of external sustainability of Ukraine’s economy, noise-signal ratios and probabilities of the occurrence of unsustainable external perturbationsare based on signal approach. The analysis of indicators of external sustainability of Ukraine’s economy shows that most indicators are volatile relative to their average values. It is shown that most indicators of the external sustainability of Ukraine’s economy are acyclic as they are weakly correlated with the growth rate of GDP, although their turning points coincide in many cases. Procyclical indicators are the ratio of reserve assets to «broad money», the ratio of net foreign assets to GDP, the average interest rate on external government liabilities, countercyclical indicators are the ratio of reserve assets to short-term external debt, the share of external public debt denominated in foreign currency to the total amount of external government obligations (except for SDR).